Analysis of Genetic Diversity of Cherry Germplasm Resources in Shandong Yantai Based on SSR Technology - Zhao CAO; Chaoran SONG; Du CHEN; Xiaofeng CHEN (Guangdong nongye kexue)
【Objective】The genetic diversity and genetic relationship of cherry germplasm in Shandong Yantai were analyzed, with an aim to provide a scientific basis for the identification and utilization of sweet cherry germplasm resources.【Method】Thirty-one main sweet cherry varieties and 5 wild nanking cherry germplasms in Yantai area were used as test materials, and primers with good polymorphism were preliminarily screened by PCR amplification technology; 36 cherry germplasms in Yantai were detected by simple sequence repeat (SSR) technology, the DNA molecular ID cards and fingerprints of cherry germplasms were constructed, and the genetic diversity and genetic structure cluster analysis were carried out.【Result】Among the 36 tested cherry germplasms, 8 pairs of SSR primers with good polymorphisms were screened, a total of 73 alleles were detected, an average of 9.12 were amplified in each pair of premiers, the Shannon index was 1.25, the Nei's gene diversity index was 0.58, and the polymorphism information content (PIC) was 0.55 on average, indicating that the cherry germplasm in Yantai area had significant genetic differences and rich genetic diversity. The SSR amplification bands were analyzed and encoded, and the molecular ID cards and fingerprints of 36 cherry germplasms were successfully constructed. The UPGMA method was used to construct a cluster analysis map, and the 36 cherry germplasms were divided into two categories: Sweet cherry and wild nanking cherry at the genetic coefficient of 0.170, indicating that the genetic relationship between wild nanking cherry and sweet cherry germplasm was obviously distant; at the genetic coefficient of 0.556, the 36 cherry germplasms could be divided into 7 categories, the r-value was 0.93, and the analysis results were consistent with the fingerprint. For the 31 sweet cherry germplasms in Yantai area, at the genetic coefficient of 0.611, they could be redivided into 5 categories, and the clustering results were in good agreement with the clustering of categories based on agronomic morphological characteristics and ripening season.【Conclusion】The polymorphisms of the selected primers were good, and they could be preferred in the genetic diversity analysis, fingerprint construction and cluster analysis of cherry germplasm. The results of this study can provide strong support for the identification of sweet cherry germplasms and the conservation of genetic diversity in Yantai area, and provide an important reference for its breeding selection and genetic structure analysis.